The Determinants of Healthcare Cost for Glaucoma Patients in Cicendo Eye Hospital, Bandung, Indonesia - Rahmah Nur Rizki; Estro Dariatno Sihaloho (Faculty of Public Health, Hasanuddin University, Makassar, 2020)
Glaucoma is the second foremost cause of impaired vision. People whosuffered from Glaucoma face the independent expenditure for thetreatment as blind people with Glaucoma could not be cured perfectly.This study intends to analyze the effect of age, types of patient care, typesof Glaucoma, and types of payment on the total cost of care of glaucomapatients at Cicendo Eye Hospital, Bandung, Indonesia. This study uses3,358 patient medical records of Cicendo Eye Hospital, Bandung,Indonesia, in 2018. The 3,358 samples were selected from the patient’smedical record based on patients’ categories indicated or convicted ofhaving Glaucoma. Robust Linear Regression is applied in this study tomeasure the additional cost for Glaucoma treatment. The results showedthat the total cost of patient care was positively and significantly affectedby hospitalization status (p=0.000), age (p=0.000), times of treatment(p=0.000), having primary glaucoma (p=0.000), having congenitalglaucoma (p=0.000), and presence of intraocular (p=0.000). Conversely,patient care’s total cost was negatively and significantly affected usinginsurance (p=0.082). This result would be a precautionary measure forthe medical institution to consider better financial planning, servicedelivery improvement, and the patient’s payment scheme effectiveness.